108k views
1 vote
Substitution
1.y=-5x-19
y=-6x-24

2.y=-6x-22
y=-3x-10

1 Answer

3 votes

Answer:

1. y=5 and x=-5

2. y=2 and x=-4

Explanation:

1.y=-5x-19

y=-6x-24

since both equations are equal to y, they are also equal to eachother

-5x-19=-6x-24

addition P.O.E.

x-19=-24

addition P.O.E.

x=-5

substitute x into one equation

y=-5*-5-19

y=6

2. y=-6x-22

y=-3x-10

since both equations are equal to y, they are also equal to eachother

-6x-22=-3x-10

addition P.O.E.

-22=3x-10

addition P.O.E.

-12=3x

division P.O.E.

-4=x

substitute x into one equation

y=-3*-4-10

y=2

User Lance Lefebure
by
4.6k points